Developing Teaching Materials on Basic Social Studies Concepts Through SDGs-Integrated Case Studies for Prospective Teachers - Nafisah, Durrotun; Marzuqi, Muhammad Ilyas; Prastiyono, Hendi; Niswatin, Niswatin; Asnimawati, Asnimawati (Universitas Pendidikan Mandalika, 2025)
This study aims to describe the development of teaching materials for basic concepts of social studies integrated with SDGs for prospective social studies teachers. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data was collected using questionnaire and test methods. The data analysis techniques used were qualitative and quantitative analysis. The results of the study showed: (1) based on the validity test, the teaching materials on the basic concepts of social studies using a case study approach were classified as very valid with a score of 82.92%; (2) the practicality test indicated that the teaching materials were very practical with a score of 83.39%; and (3) the effectiveness test, which aimed to measure the critical thinking skills of prospective social studies teachers, revealed an N-Gain score of 0.56, categorized as a moderate effect. In addition, the results of the t-test showed a significance value of 0.000, which is smaller than 0.05, indicating a significant influence of the developed teaching materials on students’ critical thinking skills. Therefore, the development of teaching materials on the basic concepts of social studies based on case studies is valid, practical, and effective for use in the learning process.